Comportamiento productivo del híbrido de maíz dekalb 5005 fertilizado orgánicamente en época seca - Demera Buste, Erwin Isidro (2011)
This research was conducted between the months of May through August during the dry season of 2010, the hacienda "San Carlos", located at Km 28 via Quevedo - Santo Domingo, whose coordinates are as follows : 79 º 29 'west longitude and 0 ° 52' south latitude at an altitude of 120 meters. General It's aim: To evaluate the productive performance of maize hybrid Dekalb fertilized organically in the dry season and specific: a) determine the effect of organic fertilizer levels in maize b) Establish the cost / benefit ratio of treatments under study. Subject to the hypotheses: a) One of the source levels of organic nutrients present the best production results and b) One of the treatments with organic abonadura present the best cost / benefit ratio. Experimental design was used DBCA randomized block with four treatments and five replications. To determine the differences between the treatment means was used multiple range test of Tukey (P <0.05). The application of chemical fertilizer (control) showed better results in plant height at 30 and 60 days, ear insertion height, length and diameter of the ear, weight of 1000 seeds (g) and yield (kg ha-1) compared with treatments compost. Despite having obtained unsatisfactory results in productive organic treatments compared with the control treatment, if positive net income obtained in these treatments, especially in treatments with doses of 500 and 1000 kg ha-1 compost with values 0.35 and 0.36. This evidence could be produced profitably preserved for a longer amount of time the quality of the soil, keeping it free of chemical residues